2023
DOI: 10.1101/2023.01.26.522174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering sources of PET signals in the tumor microenvironment of glioblastoma at cellular resolution

Abstract: Various cellular sources hamper interpretation of positron-emission-tomography (PET) biomarkers in the tumor microenvironment (TME). We developed immunomagnetic cell sorting after in vivo radiotracer injection (scRadiotracing) in combination with 3D-histology via tissue clearing to dissect the cellular allocation of PET signals in the TME. In SB28 glioblastoma mice, translocator protein (TSPO) radiotracer uptake per tumor cell was higher compared to tumor-associated microglia/macrophages (TAMs). Cellular radio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…We note that human TSPO-PET signal changes in tissue distant of the tumor could still be influenced by infiltrating tumor cells, which even exceeded the cellular uptake of the same TSPO tracer compared to myeloid cells (31). To minimize this potential impact of tumor cell invasion on TSPO expression, we focused on the contralateral hemisphere and used only tumors without bilateral manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…We note that human TSPO-PET signal changes in tissue distant of the tumor could still be influenced by infiltrating tumor cells, which even exceeded the cellular uptake of the same TSPO tracer compared to myeloid cells (31). To minimize this potential impact of tumor cell invasion on TSPO expression, we focused on the contralateral hemisphere and used only tumors without bilateral manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…reactive astrocytes. As a major novelty, we applied cell sorting after in vivo tracer injection (22)(23)(24) to a tau radiotracer. Here we found that i) tau tracer binding was tremendously higher in neurons when compared to astrocytes, ii) neurons of PS19 mice had nearly 2-fold higher tracer uptake when compared to neurons of wild-type mice, and iii) single cell tracer uptake determined the in vivo tau-PET signal.…”
Section: Discussionmentioning
confidence: 99%
“…scRadiotracing data in PS19 mice were in line with immunohistochemistry which also determined neurons as the major tau-positive cell type. Future work could directly correlate cellular radiotracer binding with the cellular amount of tau protein (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations